RELATIONSHIP BETWEEN LEVEL OF DISASTER KNOWLEDGE AND ATTITUDE OF LANDSLIDE DISASTER PREPAREDNESS IN VOLUNTEERS "KELURAHAN TANGGUHâ€ IN MALANG CITY - Ika Setyo Rini; Niko Dima Kristianingrum; Rizka Widyastikasari (Journal of Nursing Science Update (JNSU), 2019)
Indonesia is located between the Eurasian Continent Plate, the Indian-Australian Plate and the Pacific Ocean Plate. It is passed through a series of Mediterranean Circuits and the Pacific Circum. The process of plate and volcanic activity results in natural disasters including landslides. Indonesia has 918 vulnerable location points that are spread in various parts of Indonesia which cause natural disasters in Indonesia to increase every year. BPBD of Malang Citymade a program â€œKelurahan Tangguhâ€ to improve community preparedness against disasters. The purpose of this study was to explore the relationship between landslide disaster preparedness knowledge andattitude on volunteers of â€œKelurahan Tangguhâ€ in KotaLama, Bandungrejosari and Polehan because these three villages experienced the most landslides during 2018. The design of this research is observational correlational analytic with cross sectional research. The research respondents were 39 volunteers in Kotalama, Bandungrejosari and Polehan with a total sampling method. Data were collected using a questionnaire to determine the level of knowledge and attitudes of preparedness. Data analysis used Spearmanâ€™s rank correlation test. The results of the study state that there is a relationship between the level of knowledge and attitudes of preparedness. There is a positive relationship between the level of knowledge with landslide preparedness attitudes (p = 0.000, Î± = 0.05), r = 0.610. There is a undirectional relationship between the level of knowledge and attitudes of preparedness for landslides. Health workers, especially nurses and other professionals can partner with BPBD to actively conduct education, motivation and various training for volunteer empowerment in disaster preparedness in Malang City